PENGEMBANGAN MEDIA PEMEBLAJARAN MINI BOOK BERBASIS PROBLEM BASED LEARNING PADA MATERI PEMANASAN GLOBL KELAS X SMAN 6 PALOPO - Arista, Ririn; Khaerati; Muhajirah Yunus, Nur; Nurasia (Jurnal Biogenerasi, 2025)
This study aims to develop and examine the validity, practicality, and effectiveness of a mini book learning media based on Problem Based Learning (PBL) for the topic of Global Warming in Grade X at SMAN 6 Palopo. The research method used is Research and Development (R&D) with the Borg and Gall development model, which was simplified into six stages. The sample was selected using simple random sampling, namely class X Hasanuddin. The research instruments consisted of validation sheets, questionnaires, and learning outcome tests. Data analysis techniques included tests of validity, practicality, and effectiveness. The results showed that: (1) the media expert validation reached 86.25% and the material expert validation reached 91.25%, both categorized as very valid; (2) practicality based on teacher responses reached 97.50% and student questionnaire responses reached 85.50%, both categorized as very practical; and (3) the effectiveness of the mini book based on PBL reached 87.50%, categorized as very effective. Based on these results, it can be concluded that the PBL-based mini book is feasible to be used as a learning media for the topic of Global Warming at SMAN 6 Palopo.